Development Of A Learning Assesment Model For Pancasila ‎Education Based On Marzano’s Taxonomy - Hermi Yanzi; Ana Mentari Ana Mentari; Rohman Rohman; Elisa Seftiyana Elisa Seftiyana (JPI: Jurnal Pustaka Indonesia, 2026)
This study aimed to develop and evaluate a Marzano’s Taxonomy–based assessment model for Pancasila Education that measures students’ cognitive, metacognitive, and self-system competencies. The model was needed because existing assessments under the Merdeka Curriculum predominantly measured retrieval and comprehension, while higher-order thinking, self-reflection, and character-related dimensions remained insufficiently assessed. This Research and Development study employed a modified 3D model comprising Define, Design, and Develop stages. It was conducted at SMA YP Unila, Bandar Lampung, during the 2025/2026 academic year. The needs analysis involved two Pancasila Education teachers and 60 tenth-grade students. Three experts validated the developed product, followed by a limited trial involving 30 students and a field trial involving 60 students. Data were collected through interviews, needs-analysis questionnaires, validation sheets, teacher and student response questionnaires, and documentation. Qualitative data were analyzed interactively, while quantitative data were analyzed descriptively using percentages. The results showed that 80.00% of existing assessment items measured retrieval and comprehension, whereas metacognitive and self-system levels were not represented. The developed model comprised 30 items distributed across six Marzano levels and was supported by a guidebook, test and non-test instruments, rubrics, and scoring guidelines. Expert validation reached 93.42%, teacher practicality reached 92.75%, student practicality reached 92.00%, and overall feasibility reached 92.72%. These findings indicate that the model provides a more comprehensive assessment alternative for critical thinking, decision-making, self-reflection, and the internalization of Pancasila values. The study was limited to one school and did not test learning effects; future research should examine its effectiveness across diverse educational settings.